Antecedents of organizational commitment: a systematic literature review - Savita. S. Rai; Navin Kumar Koodamara; Vidyavathi K (Cogent Business & Management)
This evidence-based Systematic Literature Review (SLR) comprehensively examines existing research on the connections between organizational commitment (OC), trust, and leadership. Additionally, this study explores the theories underlying the relationships among these variables. Previous research has extensively discussed OC, but there is a need for more empirical evidence regarding its theories and antecedents. Therefore, it is essential to identify, critically analyze, and synthesize the available literature from various geographical regions. This review identified ten different theories used within the OC model. Analysis of publications between 1985 and 2023 revealed that 2011 had the highest number of publications (N = 26) on this subject. Most articles concerning individual behavioral theories in model development were based on empirical research. Furthermore, Google Scholar emerged as the most frequently used database, while SCOPUS was the most considered indexing body among researchers. As expected, the USA topped the list of publications, followed by the UK and India. This systematic review will help practitioners and researchers identify key factors and theories essential for developing a comprehensive model of OC.